If it's not what You are looking for type in the equation solver your own equation and let us solve it.
9=h/4
We move all terms to the left:
9-(h/4)=0
We add all the numbers together, and all the variables
-(+h/4)+9=0
We get rid of parentheses
-h/4+9=0
We multiply all the terms by the denominator
-h+9*4=0
We add all the numbers together, and all the variables
-1h+36=0
We move all terms containing h to the left, all other terms to the right
-h=-36
h=-36/-1
h=+36
| 7(9–n)=70 | | 6x+-4=-2x+-2 | | 15x+(10x+15)=180 | | 10x=8-7x=23 | | 5-k+1=1 | | 3x/10-×/6=2 | | 0.5/x=0.05 | | 3^x-2=5^2x | | 3x-4=2x*1 | | 5x-4=26+3x | | 18x-22=x+63 | | 6y-5+2y=37 | | (3+n)(7)=-28 | | -(2m-8)=-2 | | 51=pX300 | | 8y-6y+15y=48 | | 2u+11=19 | | 13+1x=40 | | 9x-16=23 | | 5n-2n=-24 | | c-8/4=2 | | 3(8-x)=36-5x | | -3c+-6c=18 | | 6x+25=150 | | 0.89+30x=1.39x | | P=1.25n | | 5n-2n=24 | | 8x=2(9x-85) | | 3x(x=2)=18 | | 13g+7g-12=8 | | -8m+-12m=20 | | 146=25y+11 |